The teacher’s authority in education - Cieśleńska, Beata (Annales Universitatis Paedagogicae Cracoviensis. Studia ad Didacticam Scientiarum Socialium Pertinentia, 2022)
The authority of the teacher is an important issue in contemporary pedeutology. It relates to the professionalism, vocation and personality of the educator. The relationship that teachers, considered to be an authority, will create with their students may affect not only the acquisition of knowledge, but most of all their perception of the surrounding reality. The article presents the key concepts of authority, its classification and criteria. The place of authority in education has been shown, paying attention to the process of its formation. Attention was paid to the democratic authority that allows for protection against failures, which facilitate the achievement of success for pupils. The principles on which the teacher’s authority should be based were also shown.